Quality of Service of Routing Protocols in Wireless Sensor Networks: A Review - Muhammad Asif; Shafiullah Khan; Rashid Ahmad; Muhammad Sohail; Dhananjay Singh (IEEE Access)
Due to distributed nature, dynamic topology and resources constraints of tiny sensing nodes in wireless sensor networks (WSNs), the quality of service (QoS) support is a challenging issue. However, satisfying the stringent QoS requirements is an open problem. QoS aware protocols for WSNs have gained recently considerable attention of the researchers. In this paper, we focus on the QoS satisfaction in WSNs, basics of QoS support in WSNs, and more importantly challenge, requirements of QoS at each layer. Furthermore, we review the QoS protocols and categorize the QoS aware protocols and elaborate their pros and cons. We also discuss the QoS parameters with respect to each protocol performance parameters. A survey and comprehensive discussion on the QoS aware protocols of WSNs are presented, including their strengths and limitations. Finally, we also survey some computational intelligence (CI) techniques and find the basic requirements of such techniques. Moreover, we study these CI techniques in the light of QoS management and tabulate the level of each CI technique for QoS management. The paper is concluded with open research issues.